Strategi Pengembangan Pariwisata Melalui Perencanaan â€Rest Areaâ€ Berbasis Masyarakat di Kawasan Pesisir Pantai Desa Sebong Pereh-Kabupaten Bintan - Yudy Sunantri; Henricus Yayan (Bahtera Inovasi, 2021)
Sebong Pereh Village is one of the villages traversed by the Tanjung Uban-Lagoi road, Bintan Regency. This road is a main road which connects tourists to Lagoi tourist area. Along this road has tourism potential which could be developed because of its location on the coast. The development of tourism planning for the rest area at this location requires the role of the community, especially the residents of Sebong Pereh Village themselves. Community participation is also one of the keys in planning the construction of this rest area where local residents themselves will manage the place. The knowledge and perception of residents regarding the concept of a rest area is also one of the basis for planning this tourism activity. Based on the results of the questionnaire, the community agreed with the construction of a rest area in the area. Geographical factors, facilities, and attractions are some that need to be considered. In addition, this community-based rest area also requires support from various parties such as relevant stakeholders and the government